Some Properties of Binormal Operators - Hassan, Hadeel Ali (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper we have introduced some classes of operators like class of normal operators and n-binormal operators and n-isometry operators on an infinite Hilbert space H. We have given some basic properties of these classes of operators. In general, every normal operator is not necessarily an isometry operator and we studied the relationship between normal with n-isometry and normal with n-binormal .We concluded the relationship between n-isometry with n-binormal.
Keywords: Normal operator; nNormal operator; Binormal operator